An Empirical Examination of Unemployment Invariance Hypothesis, Discouraged and Added Worker Effects in Turkey - Arisoy, Ibrahim (International Journal of Economics and Financial Issues, 2018)
This paper examines the long run relationship between unemployment and labor force participation rates as a criterion for assessing the validity of discouraged effect or unemployment invariance hypothesis in Turkish labor market for the period 2000Q1-2011Q3. To this end, ARDL bounds testing and Gregory and Hansen cointegration methods are utilized to test for the long run relationship between unemployment and labor force participation rates. The empirical results indicate that there is no evidence of a long run relationship between unemployment and labor force participation rates by using both aggregate and disaggregated data and thus long run unemployment rate is independent of labor force participation rate in Turkey. Keywords: Unemployment invariance hypothesis, discouraged worker effect, labor force participation rates, unemployment, cointegration. JEL Classifications: C22, E24, J60 DOI: https://doi.org/10.32479/ijefi.7127